Standard Operating Procedures for Governed Master Data Consolidation in EBX5 - Kinshuk Dutta (International Journal of Intelligent Systems and Applications in Engineering, 2018)
Master data consolidation programs often fail not because the target platform lacks technical capability, but because operating controls, role boundaries, stewardship procedures, and exception-handling patterns are not formalized early enough. This paper presents a standard operating procedure (SOP) framework for governed data consolidation using EBX5. The framework defines a repeatable operating model for receiving data from source systems, validating and loading records into a landing zone, transforming and standardizing records through staging, applying matching and survivorship rules, resolving ambiguous clusters through stewardship, and publishing governed golden records. The paper emphasizes the separation of automated system tasks from accountable user tasks, the importance of stewardship role design, and the controlled onboarding of new data providers. The result is a practical governance-oriented architecture for reducing implementation variability and improving repeatability in multi-domain master data management deployments. DOI: https://doi.org/10.17762/ijisae.v6i4.8347